Pengaruh Lama Waktu Fermentasi terhadap Aktivitas Antioksidan pada Minuman Kopi Hijau Arabika Probiotik (Coffea arabica L.) sebagai Minuman Fungsional - Marco, Martha Aulia; Lestari, Catur Retno; Rarastiti, Chairunnisa Nur (Indonesian Journal of Nutrition Science and Food; Vol 4 No 2 (2025): Januari 2025, 2025)
Functional drinks are one of the types of functional foods. Functional drinks can be sourced from natural ingredients, namely plant materials. Plant materials that have antioxidant content are not only found in fruits and vegetables but also coffee beans. In addition to coffee which has antioxidant properties, there are also probiotics. An alternative way to get the benefits of green arabica coffee and probiotics with natural antioxidant content is to make it a functional drink, namely probiotic green arabica coffee drinks. This study aims to determine the effect of fermentation time on antioxidant activity in probiotic green arabica coffee drinks as functional drinks. This study is an experimental laboratory study that seeks to test the antioxidant activity of DPPH as an antioxidant capacity in three probiotic green arabica coffee formulations, as well as chemical analysis, namely measuring the degree of acidity (pH) using a pH meter. The data obtained were subjected to analysis of variance (Analysis of Variate ANOVA) with a confidence level of p <0.05 to prove a significant effect between the formulation of probiotic green arabica coffee drinks and antioxidant activity. The study's results proved that the lowest pH value and higest antioxidant activity levels were found in samples fermented for 24 hours, which were 5 and 9948.5972 ppm. The study contributed to opening up opportunities for the development of food ingredients into functional foods .